Inflow-modulated inputs of dissolved organic matter fuel carbon dioxide emissions from a large hyper-eutrophic lake - Mingrui Qian; Yongqiang Zhou; Lei Zhou; Yunlin Zhang; Yang Pu; Travis W. Drake; Thomas A. Davidson; Robert G.M. Spencer; Justin D. Brookes; Erik Jeppesen (Water Research, 2025)

Hydrology drives export and composition of carbon in a pristine tropical river - Travis W. Drake; Matti Barthel; Christian Ekemba Mbongo; Davin Mata Mpambi; Simon Baumgartner; Clement Ikene Botefa; Marijn Bauters; Martin R. Kurek; Robert G. M. Spencer; Amy M. McKenna; Negar Haghipour; Godé Lompoko Ekamba; et al. (Limnology and Oceanography, 2023)
The Ruki is a pristine blackwater tributary in the Congo Basin draining tropical lowland forest. Daily discharge and fortnightly concentrations, isotopic ratios, and molecular composition of carbon and organic matter were measured for 1 yr (2019–2020). Like the Congo River, discharge peaked from November–January, with a smaller secondary peak in June. Dissolved organic carbon (DOC), inorganic carbon (DIC), carbon dioxide ( p CO 2 ), and methane ( p CH 4 ) concentrations were high (21.3 ± 4.8 mg C L −1 , 5.8 ± 0.9 mg C L −1 , 6370 ± 1740 ppm, and 250 ± 100 ppm, respectively) and positively correlated with discharge, indicating transport limitation. Total suspended solids and particulate organic carbon (POC) concentrations were generally low (3.68 ± 1.61 mg L −1 , 0.88 ± 0.33 mg C L −1 , respectively) and varied inversely with discharge, indicating source limitation. The Ruki exported a total of 3.25 Tg C yr −1 , of which DOC, DIC, and POC comprised 76%, 20%, and 3%, respectively. This DOC flux represents ~ 20% of the annual Congo Basin flux from about 5% of its area, highlighting the high yield. Isotopic ratios of DOC and POC indicate modern C3 forest vegetation as a source, except for a few older samples potentially indicating peat inputs. The bulk molecular composition of dissolved organic matter was seasonally consistent; however, a more oxidized and aromatic assemblage occurred at high discharge, corresponding with forest vegetation, while a more aliphatic, nitrogen‐, and sulfur‐enriched assemblage was found during low discharge, corresponding with soil‐derived organic matter. Overall, these results underscore how hydrology controls C concentrations in the Ruki River and how this blackwater river contributes disproportionately to C export per unit area within the Congo Basin hydrosystem.

Substantial Organic and Particulate Nitrogen and Phosphorus Export from Geomorphologically Stable African Tropical Forest Landscapes - Simon Baumgartner; Marijn Bauters; Travis W. Drake; Matti Barthel; Serge Alebadwa; Nadine Bahizire; Basile Mujinya Bazirake; Johan Six; Pascal Boeckx; Kristof Van Oost (Ecosystems, 2023)

The Impact of Surface Temperature Heterogeneity on Near-Surface Heat Transport - Travis Morrison; Marc Calaf; Chad W. Higgins; Stephen A. Drake; Alexei Perelet; Eric Pardyjak (Boundary-Layer Meteorology, 2021)

Century‐long apparent decrease in intrinsic water‐use efficiency with no evidence of progressive nutrient limitation in African tropical forests - Marijn Bauters; Sofie Meeus; Matti Barthel; Piet Stoffelen; Hannes P. T. De Deurwaerder; Félicien Meunier; Travis W. Drake; Quentin Ponette; Jerôme Ebuy; Pieter Vermeir; Hans Beeckman; Francis wyffels; et al. (Global Change Biology, 2020)
Forests exhibit leaf‐ and ecosystem‐level responses to environmental changes. Specifically, rising carbon dioxide (CO 2 ) levels over the past century are expected to have increased the intrinsic water‐use efficiency (iWUE) of tropical trees while the ecosystem is gradually pushed into progressive nutrient limitation. Due to the long‐term character of these changes, however, observational datasets to validate both paradigms are limited in space and time. In this study, we used a unique herbarium record to go back nearly a century and show that despite the rise in CO 2 concentrations, iWUE has decreased in central African tropical trees in the Congo Basin. Although we find evidence that points to leaf‐level adaptation to increasing CO 2 —that is, increasing photosynthesis‐related nutrients and decreasing maximum stomatal conductance, a decrease in leaf δ 13 C clearly indicates a decreasing iWUE over time. Additionally, the stoichiometric carbon to nitrogen and nitrogen to phosphorus ratios in the leaves show no sign of progressive nutrient limitation as they have remained constant since 1938, which suggests that nutrients have not increasingly limited productivity in this biome. Altogether, the data suggest that other environmental factors, such as increasing temperature, might have negatively affected net photosynthesis and consequently downregulated the iWUE. Results from this study reveal that the second largest tropical forest on Earth has responded differently to recent environmental changes than expected, highlighting the need for further on‐ground monitoring in the Congo Basin.

Land‐use controls on carbon biogeochemistry in lowland streams of the Congo Basin - Travis W. Drake; David C. Podgorski; Bienvenu Dinga; Jeffrey P. Chanton; Johan Six; Robert G. M. Spencer (Global Change Biology, 2020)
The flux and composition of carbon (C) from land to rivers represents a critical component of the global C cycle as well as a powerful integrator of landscape‐level processes. In the Congo Basin, an expansive network of streams and rivers transport and cycle terrigenous C sourced from the largest swathe of pristine tropical forest on Earth. Increasing rates of deforestation and conversion to agriculture in the Basin are altering the current regime of terrestrial‐to‐aquatic biogeochemical cycling of C. To investigate the role of deforestation on dissolved organic and inorganic C (DOC and DIC, respectively) biogeochemistry in the Congo Basin, six lowland streams that drain catchments of varying forest proportion (12%–77%) were sampled monthly for 1 year. Annual mean concentrations of DOC exhibited an asymptotic response to forest loss, while DIC concentrations increased continuously with forest loss. The isotopic signature of DIC became significantly more enriched with deforestation, indicating a shift in source and processes controlling DIC production. The composition of dissolved organic matter (DOM), as revealed by ultra‐high‐resolution mass spectrometry, indicated that deforested catchments export relatively more aliphatic and heteroatomic DOM sourced from microbial biomass in soils. The DOM compositional results imply that DOM from the deforested sites is more biolabile than DOM from the forest, consistent with the corresponding elevated stream CO 2 concentrations. In short, forest loss results in significant and comprehensive shifts in the C biogeochemistry of the associated streams. It is apparent that land‐use conversion has the potential to dramatically affect the C cycle in the Congo Basin by reducing the downstream flux of stable, vascular‐plant derived DOC while increasing the transfer of biolabile soil C to the atmosphere.

Multidecadal climate‐induced changes in Arctic tundra lake geochemistry and geomorphology - Travis W. Drake; Robert M. Holmes; Alexander V. Zhulidov; Tatiana Gurtovaya; Peter A. Raymond; James W. McClelland; Robert G. M. Spencer (Limnology and Oceanography, 2019)
High‐latitude lakes are sensitive indicators of climate and important ecological components of Northern landscapes. The response of Arctic lakes to accelerated 20 th century warming has largely been inferred from paleolimnological and shorter‐term observational studies ( p CO 2 , measured during the ice‐free period in late summer, increased over time. Over the same period, the rates of primary and bacterial production increased significantly. Permafrost thaw at the base and margins of the lakes likely resulted in the observed increase in size, as measured by average depth, surface area, and total volume. The observed changes show strong correlation with temperature, suggesting an overall pronounced response to warming. Importantly, CO 2 sourced from either in situ or allochthonous respiration of thawed permafrost would indicate the destabilization of a large C reservoir.